2012
DOI: 10.1038/nchem.1452
|View full text |Cite
|
Sign up to set email alerts
|

Engaging unactivated alkyl, alkenyl and aryl iodides in visible-light-mediated free radical reactions

Abstract: Radical reactions are a powerful class of chemical transformations. However, the formation of radical species to initiate these reactions has often required the use of stoichiometric amounts of toxic reagents, such as tributyltin hydride. Recently, the use of visible-light-mediated photoredox catalysis to generate radical species has become popular, but the scope of these radical precursors has been limited. Here, we describe the identification of reaction conditions under which photocatalysts such as fac-Ir(p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
330
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 681 publications
(344 citation statements)
references
References 52 publications
6
330
0
1
Order By: Relevance
“…A trace of elimination product 11 ($5%) could be seen in case of chloride substrate 10a while bromide 2 gave about 10% of 11. Interestingly, the reaction of iodide 10b [54] was faster and completed within 35 min but accompanied with about 30% of alkene 11. Although the elimination product 11 is easily separable from the desired fluoride 8a, its yield was affected to varied extent depending on the substrate.…”
Section: Resultsmentioning
confidence: 97%
“…A trace of elimination product 11 ($5%) could be seen in case of chloride substrate 10a while bromide 2 gave about 10% of 11. Interestingly, the reaction of iodide 10b [54] was faster and completed within 35 min but accompanied with about 30% of alkene 11. Although the elimination product 11 is easily separable from the desired fluoride 8a, its yield was affected to varied extent depending on the substrate.…”
Section: Resultsmentioning
confidence: 97%
“…[26] It was reported that the redox potentials of homogeneous transition-metal-based organometallicc omplexes can be adjusted by modifyingt he metal center and/ors urrounding ligands to meet the activation energy of specific organic reactions. [27] Similarly,t he effective valence( VB) and conduction band (CB) positions of heterogeneous inorganic photocatalytic systemsc an also be adjusted by forming hybrid-o rh eterostructures with variousm etals to achieve enhanced photoactivity. [28] Ar ecent study on CMPs demonstrated that the geometry design of the 3D polymer network structure played an crucial role in improving the photocatalytic efficiencies of the CMP photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[15] A series of Oacyl oximes 1 a-h with different acyl groups were prepared, and their ability to form phenanthrine 2 a via an iminyl radical under visible-light catalysis was evaluated (Scheme 3). When O-acyl oximes 1 a-e were irradiated with visible light in the presence of fac-[Ir(ppy) 3 ] in DMF, the starting materials were fully recovered.…”
mentioning
confidence: 99%